2022
DOI: 10.1155/2022/1974467
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Expansion: A Comparison of Damon Self-Ligating Bracket Therapy with MARPE and PAOO

Abstract: Purpose. The aim of this study was to investigate arch parameters and dentoalveolar changes from pretreatment to posttreatment by comparing the Miniscrew Assisted Rapid Palatal Expansion (MARPE), Periodontally Accelerated Osteogenic Orthodontics (PAOO), and Damon self-ligating bracket therapies. Materials and Methods. Seventy-nine patients underwent maxillary expansion followed by or in conjunction with Damon ( n = 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…2-3). Five studies showed a moderate risk of bias [19,31,32,34,35], while the rest seven studies were at a serious risk of bias [15,[26][27][28][29][30]33]. The main risk of bias comes from bias due to confounding, selection of participants, measurement of outcomes, and selection of the reported results.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…2-3). Five studies showed a moderate risk of bias [19,31,32,34,35], while the rest seven studies were at a serious risk of bias [15,[26][27][28][29][30]33]. The main risk of bias comes from bias due to confounding, selection of participants, measurement of outcomes, and selection of the reported results.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…Nine studies reported the changes in dental transverse widths with nasomaxillary complex expansion [15,27,[29][30][31][32][33][34][35]. Five studies included the intercanine width (ICW) [31][32][33][34][35], ve reported inter-rst premolar width (IP1W) [15,29,[33][34][35], ve reported inter-second premolar width (IP2W) [15,29,[33][34][35], and nine included the intermolar width (IMW) [15,27,[29][30][31][32][33][34][35]. The mean ICW range was 2.30 to 5.83 mm, the mean IP1W range was 3.00 to 5.33 mm, the mean IP1W range was 3.44 to 5.66 mm, and the mean IMW range was 3.46 to 7.33 mm.…”
Section: Dental Transverse Expansionmentioning
confidence: 99%
See 3 more Smart Citations